Amelia's bff : best friends forever, best friends fighting, best friends for now? - Moss, Marissa (Simon & Schuster Books for Young Readers, 2011)
Amerlia thought that the only thing better than a best friend was two best friends. But then they come together and she's not sure if any of them are friends. Will Amelia be able to have more than one best friend?